Environmental Crime - Amar Mubarok (UM Purwokerto Press, 2023)
Environmental crime is a serious threat to ecosystem sustainability and people's welfare in Indonesia. This paper aims to describe various forms of environmental crimes that have occurred in Indonesia, explore the causal factors, and analyze law enforcement efforts in tackling these crimes. By understanding the traces of crime and the challenges it faces, this paper provides an overview of the importance of strengthening the law enforcement system and cooperation between various stakeholders in protecting the environment.